CONE BEAM COMPUTED TOMOGRAPHY IMAGING CHARACTERISTICS OF MANDIBULAR DENTIGEROUS CYSTS AND POSSIBLE IMAGING FEATURES ASSOCIATED WITH BONE EXPANSION - Gökçen Akçiçek; Leyla Berna Çağırankaya; Nursel Akkaya; Hatice Yağmur Zengin (Sabiad)
Objective: Dentigerous cysts (DC) are one of the most common cysts in the jaw, and radiographic features are important for diagnosis. This study aims to evaluate the radiographic features of mandibular DCs on cone beam computed tomography (CBCT) images and investigate the possible associations between the imaging features and bone expansion. Material and Methods: Patients who had CBCT images with pathologically proven DC within the mandible were included the study. On CBCT images, besides lesion radiographic features, the position of the impacted tooth and cyst-to-crown relationship were also recorded. Results: Among 36 DCs, 69.4% affected the impacted tooth (61.1% were displaced, 5.6% were resorbed and 2.8% were both displaced and resorbed), 80.6% expanded, 100% had cortical involvement (perforation and thinning), 80.6% affected the inferior alveolar canal (%13.9 resorption, %11.1 displacement, 55.6% resorption and displacement), 65.7% affected the adjacent teeth (27.8% resorption, 30.6% lamina dura loss, 5.6% displacement and lamina dura loss), 25% of impacted tooth position were in buccal/lingual obliquity, and 55.5% had a lateral type cyst-to-crown relationship. There was a statistically significant relationship between the expansion rate and effect on the impacted tooth (p=0.023), between the expansion rate and effect on the adjacent tooth (p=0.011), and between the cyst-to-crown relationship and impacted tooth buccolingual position (p=0.031). Conclusion: Resorption and displacement of the impacted tooth and resorption, displacement and lamina dura loss of the adjacent tooth were common and statistically related with DCs expansion rates. These imaging features could be a sign of expansion and should be carefully examined.